Implementation Of Strengthening Character Education In Learning At Syubbanul Wathon Middle School Magelang - Jazimatussoimah, Jazimatussoimah; Siswanto, Siswanto (Mudir : Jurnal Manajemen Pendidikan, 2024)
Strengthening character education has become the main focus in the world of education as an effort to prepare the younger generation with strong moral values. This research aims to explore the implementation of strengthening character education in the learning process at Syubbanul Wathon Middle School in Magelang. A qualitative approach was used to gain an in-depth understanding of the strategic steps that the school has adopted in strengthening character learning. The research method involves collecting data through interviews with school administrators, teachers, and educational staff. In addition, direct observation is carried out to observe the implementation of programs that support student character development in the learning environment. The research results show that the implementation of strengthening character education at Syubbanul Wathon Middle School involves several main strategies. One of them is the preparation of a curriculum that incorporates character values into every subject, emphasizing the importance of developing teachers to be examples and bearers of values for students, as well as creating a learning environment that supports character development through various school activities. Challenges faced in this implementation include limited resources and expanding the character education program to environments outside the classroom. However, these steps have made a positive contribution to the development of students' character, especially in building attitudes of responsibility, cooperation and honesty. This research provides valuable insight into effective practices in strengthening character education at the junior high school level, emphasizing the importance of the involvement of all relevant parties, including schools, teachers, students and parents. The implications of this research can provide guidance for other schools to adopt and improve similar programs to form a generation with strong and high-quality character.